Upaya Meningkatkan Kemampuan Membaca Huruf Hijaiyah Melalui Penggunaan Alat Peraga Kartu Huruf Dan Kata Pada Siswa Tuna Grahita Ringan Kelas VIII SMLB Bina Karya Insani Karanganyar Tahun Ajaran 2015/2016 - Muzayyanah, Muzayyanah, Dr. Abdullah Aly, M.Ag (2016)
Learning is made to read the letter hijaiyah in SMPLB Bina Karya Insani Karanganyar sometimes already use props but how to teach with lectures models remains a habit in the learning process. The results of learning through lecture method is not sufficient to provide optimal contribution. From this background, the formulation of the problem which arises is there increasing ability to read letters hijaiyah on students after learning with the use of props card letters and words on a lightly mentally disabled student class viii SMPLB bina karya Insani karanganyar? This study aims to determine whether the use of props letter cards can help improve the ability to read letters hijaiyah on student learning outcomes mild mentally retarded class viii SMPLB Bina Karya Insani karanganyar through props letter cards second semester of academic year 2015/2016. The subjects used in this study were students of class VIII mentally disabled SMPLB Bina Karya Insani Karanganyar second semester of academic year 2015/2016. Number of students studied were 7 students, consisted of 5 male students and two female students. While the object is a class VIII student learning outcomes in the form of letters hijaiyah reading skills through tools perga letter card. Forms of this research is the Classroom Action Research (PTK) is conducted in two cycles. Each cycle consists of four stages: planning, implementing / action, observation, and reflection. Data collection techniques used were tests, interviews, and observations. In this study, the data analysis technique used is the technique of interactive analysis.Based on the survey results revealed that the average value of students in the initial conditions is 64 (under KKM). In the first cycle of the first meeting students' average score increased to 67.14 at the meeting II increased again to 69.28. Then in the second cycle the average value of the students at the first meeting increased again to 73 and at a meeting II to 80. The results of these studies indicate that student learning outcomes in reading ability hijaiyah letter can be optimized through props letter cards for students of classes VIII SMPLB Bina Karya Insani Karanganyar second semester of the school year 2015/2016. Therefore, props hijaiyah letter card can be used as an alternative method of learning that can be applied to the teacher to optimize learning results in the ability to read letters hijaiyah.